Decoloniality and critical literacy in a unit of an English language teaching material - Silveira, Fernanda Vieira da Rocha; Batista , Marina Maria dos Santos (The ESPecialist, 2024)
This qualitative documental research aimed to analyze the sections Getting Started, Reading Comprehension, Language in Use, and English 4 Life, in unit 2 entitled “Is she Brazilian?”, from the book English Play 6 (FRANCO; TAVARES, 2019), for Brazilian students in the sixth year of elementary school. The theoretical background that supported this study included decoloniality (MCGREGOR, 2012; OLIVEIRA; CANDAU, 2010) and critical literacy (LUKE; DOOLEY, 2011; JANKS, 2016) in the composition of multimodal texts (SÁ; MELLO, 2018), focusing on the concepts of design and redesign (JANKS, 2013) in the exercises related to the analyzed unit. Data were examined in light of content analysis (BARDIN, 1977). The results showed that the sections present initiatives of decoloniality and sociocultural contextualization with the reality of Brazilian students in the sixth year of basic education; although some stereotyped notions and gaps remain regarding diversity, critical literacy and the chances of design and redesign in multimodal texts. Thus, this work contributes to studies on didactic materials used in English teaching in Brazil, considering the development of critical thinking and agency of basic education learners.